2
$\begingroup$

I am given a damped wave equation

$u_{tt}(t,x)+2u_t(t,x)=u_{xx}(t,x); \forall t>0$

Now I know the laplace transform of this given the initial conditions,

$u(0,x)=\sin x, u_t(0,x)=0;$

is $\tilde u_{xx}(s,x)-(s^2+2s)\tilde u(s,x)+(2+s)\sin x=0$

Now to solve this, I will use method of second order linear homogenous with constant coefficients, however my question is how can solve the wave equation if I am not given any boundary conditions?

All help appreciated!

$\endgroup$

bumped to the homepage by Community 2 days ago

This question has answers that may be good or bad; the system has marked it active so that they can be reviewed.

0
$\begingroup$

Let $u=e^{-t}v$ ,

Then $u_t=e^{-t}v_t-e^{-t}v$

$u_{tt}=e^{-t}v_{tt}-e^{-t}v_t-e^{-t}v_t+e^{-t}v=e^{-t}v_{tt}-2e^{-t}v_t+e^{-t}v$

$u_x=e^{-t}v_x$

$u_{xx}=e^{-t}v_{xx}$

$\therefore e^{-t}v_{tt}-2e^{-t}v_t+e^{-t}v+2e^{-t}v_t-2e^{-t}v=e^{-t}v_{xx}$

$v_{tt}=v+v_{xx}$

Similar to Solve initial value problem for $u_{tt} - u_{xx} - u = 0$ using characteristics,

Consider $v(a,x)=f(x)$ and $v_t(a,x)=g(x)$ ,

Let $v(t,x)=\sum\limits_{n=0}^\infty\dfrac{(t-a)^n}{n!}\dfrac{\partial^nv(a,x)}{\partial t^n}$ ,

Then $v(t,x)=\sum\limits_{n=0}^\infty\dfrac{(t-a)^{2n}}{(2n)!}\dfrac{\partial^{2n}v(a,x)}{\partial t^{2n}}+\sum\limits_{n=0}^\infty\dfrac{(t-a)^{2n+1}}{(2n+1)!}\dfrac{\partial^{2n+1}v(a,x)}{\partial t^{2n+1}}$

$v_{tttt}=v_{tt}+v_{xxtt}=v+v_{xx}+v_{xx}+v_{xxxx}=v+2v_{xx}+v_{xxxx}$

Similarly, $\dfrac{\partial^{2n}v}{\partial t^{2n}}=\sum\limits_{k=0}^nC_k^n\dfrac{\partial^{2k}v}{\partial x^{2k}}$

$v_{ttt}=v_t+v_{xxt}$

$v_{ttttt}=v_{ttt}+v_{xxttt}=v_t+v_{xxt}+v_{xxt}+v_{xxxxt}=v_t+2v_{xxt}+v_{xxxxt}$

Similarly, $\dfrac{\partial^{2n+1}v}{\partial t^{2n+1}}=\sum\limits_{k=0}^nC_k^n\dfrac{\partial^{2k+1}v}{\partial x^{2k}\partial t}$

$\therefore v(t,x)=\sum\limits_{n=0}^\infty\sum\limits_{k=0}^n\dfrac{C_k^nf^{(2k)}(x)(t-a)^{2n}}{(2n)!}+\sum\limits_{n=0}^\infty\sum\limits_{k=0}^n\dfrac{C_k^ng^{(2k)}(x)(t-a)^{2n+1}}{(2n+1)!}$

Hence $u(t,x)=e^{-t}\sum\limits_{n=0}^\infty\sum\limits_{k=0}^n\dfrac{C_k^nf^{(2k)}(x)(t-a)^{2n}}{(2n)!}+e^{-t}\sum\limits_{n=0}^\infty\sum\limits_{k=0}^n\dfrac{C_k^ng^{(2k)}(x)(t-a)^{2n+1}}{(2n+1)!}$

For the case of conditions specific at $u(0,x)=\sin x$ and $u_t(0,x)=0$ ,

the corresponding conditions of $v$ are $v(0,x)=\sin x$ and $v_t(0,x)=\sin x$

$\therefore u(t,x)=e^{-t}\sin x\sum\limits_{n=0}^\infty\sum\limits_{k=0}^n\dfrac{(-1)^kC_k^nt^{2n}}{(2n)!}+e^{-t}\sin x\sum\limits_{n=0}^\infty\sum\limits_{k=0}^n\dfrac{(-1)^kC_k^nt^{2n+1}}{(2n+1)!}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.